2018
DOI: 10.4085/1062-6050-398-17
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Rates of Hyperthermic Humans Wearing American Football Uniforms When Cold-Water Immersion Is Delayed

Abstract: Context Treatment delays can be contributing factors in the deaths of American football athletes from exertional heat stroke. Ideally, clinicians begin cold-water immersion (CWI) to reduce rectal temperature (Trec) to <38.9°C within 30 minutes of collapse. If delays occur, experts recommend Trec cooling rates that exceed 0.15°C/min. Whether treatment delays affect CWI cooling rates or perceptual variables when football uniforms are worn is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This standard-of-care management strategy is easy and quick to implement. Cold-water immersion may be just as effective without removal of football padding, 13,14 yet removing protective equipment permits optimal cooling because the body surface area exposed to the cooling modality is maximized. However, if the patient is combative or exhibiting aggressive behavior, initiating cooling with protective equipment on and then removing it during the cooling process may allow for a more rapid temperature reduction.…”
Section: Removal Of Protective Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This standard-of-care management strategy is easy and quick to implement. Cold-water immersion may be just as effective without removal of football padding, 13,14 yet removing protective equipment permits optimal cooling because the body surface area exposed to the cooling modality is maximized. However, if the patient is combative or exhibiting aggressive behavior, initiating cooling with protective equipment on and then removing it during the cooling process may allow for a more rapid temperature reduction.…”
Section: Removal Of Protective Equipmentmentioning
confidence: 99%
“…[9][10][11][12] Once EHS is confirmed (rectal temperature .40.58C with obvious central nervous system dysfunction), rapid, wholebody cooling using cold-water immersion (CWI) until internal body temperature (ie, rectal temperature) reaches 38.98C is recommended before the patient is transported for higher-level medical care. 2 Researchers 13,14 have demonstrated that adequate rates of cooling (0.28C/min) can occur with CWI, even while wearing protective equipment.…”
mentioning
confidence: 99%
“…Thermal sensation 8,9 is a useful measure for determining the intensity of temperatures experienced by individuals. Similarly, the 16-item environmental symptom questionnaire (ESQ) [10][11][12] provides useful information about the severity and presence of heat-related signs or symptoms (e.g., lightheadedness, feverish). Authors have used these scales to identify whether individuals experience higher or lower degrees of thermal stress 10,13 and the usefulness of various treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Mental status and vital signs (including rectal temperature) guide the cooling treatment of exertional heat illness causalities (45,56,61,132).…”
mentioning
confidence: 99%